2020
DOI: 10.1007/s11864-020-0707-5
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer-Related Fatigue: Causes and Current Treatment Options

Abstract: Opinion statementCancer-related fatigue (CRF) is a problem for a significant proportion of cancer survivors during and after active cancer treatment. However, CRF is underdiagnosed and undertreated. Interventions are available for CRF although there is no gold standard. Based on current level of evidence, exercise seems to be most effective in preventing or ameliorating CRF during the active- and posttreatment phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
265
2
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(289 citation statements)
references
References 134 publications
(198 reference statements)
9
265
2
13
Order By: Relevance
“…Cancer-related fatigue, also known as cancer fatigue, is a highly prevalent long-term side effect among breast cancer survivors (7,8). This complex and multidimensional condition is clinically characterized by a persistent sense of physical, emotional, and/or cognitive stiffness, resulting in a substantial impairment of health-related quality of life (7,9). The etiology of breast cancer fatigue (BCF) is poorly understood and probably related to mitochondrial dysfunction, inflammation, and increased reactive oxygen species production (8,10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer-related fatigue, also known as cancer fatigue, is a highly prevalent long-term side effect among breast cancer survivors (7,8). This complex and multidimensional condition is clinically characterized by a persistent sense of physical, emotional, and/or cognitive stiffness, resulting in a substantial impairment of health-related quality of life (7,9). The etiology of breast cancer fatigue (BCF) is poorly understood and probably related to mitochondrial dysfunction, inflammation, and increased reactive oxygen species production (8,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…However, the wide subjectivity of BCF hinders further research to explain its pathogenesis. Several risk factors have been identified so far, including low socioeconomic status, sleep disturbance, emotional stress, anxiety, physical inactivity, high body mass index (BMI), radical surgery, chemotherapy, and radiotherapy (8,9). According to the American Society of Clinical Oncology (ASCO) and the National Comprehensive Cancer Network (NCCN) guidelines, specific screening programs for BCF should be performed (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BCRL involves more than 25% of breast cancer survivors, [3,4] while axillary web syndrome (AWS) after axillary lymph node dissection affects in 6 to 85.4% [5,6]. Cancer-related fatigue is a common disabling conditions in breast cancer survivors [7]. It has been estimated that approximately one-third of cancer survivors have clinically significant fatigue up to 6 years following treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Cancer-related fatigue is a common disabling conditions in breast cancer survivors. [7] It has been estimated that approximately onethird of cancer survivors have clinically signi cant fatigue up to 6 years following treatment. [8] Breast cancer survivorship care has aroused increasing attention in recent years, and the management of the above-mentioned complications are topics of concern in the rehabilitation eld.…”
Section: Introductionmentioning
confidence: 99%